Similar rebleeding rate in 3-day and 7-day intravenous ceftriaxone prophylaxis for patients with acute variceal bleeding - Tzong-Hsi Lee; Chung-Tsui Huang; Chien-Chu Lin; Chen-Shuan Chung; Cheng-Kuan Lin; Kuang-Chau Tsai (Journal of the Formosan Medical Association, 2016)
Although prophylactic antibiotics have been recommended for cirrhotic patients with upper gastrointestinal bleeding, the duration of its use remains an inconclusive issue. We designed this study to investigate the duration of antibiotic prophylaxis for cirrhotic patients with acute esophageal variceal bleeding. Methods: We enrolled those patients suffering from acute esophageal variceal bleeding and receiving band ligation. They were randomly allocated to two groups to receive prophylactic antibiotics; Group I: receiving intravenous ceftriaxone 500 mg every 12 hours for 3 days, and Group II: same regimen for 7 days. We used rebleeding rate within 14 days as the primary end point and also evaluated the survival rate within 28 days and the amount of transfusion during admission. Results: There were 38 patients in Group I and 33 patients in Group II that completed the study course for analysis. Overall, there was no significant difference in the baseline characteristics between these two groups. There were three patients both in Group I and Group II who developed rebleeding within 14 days (8% vs. 9%, p > 0.99). There was also no difference between Group I and Group II in transfusion amount (2.71 ± 2.84 units vs. 3.18 ± 4.07, p = 0.839) and survival rate in 28 days (100 vs. 97%, p = 0.465). Conclusion: Our small scale study demonstrated that there was no difference in the rebleeding rate between 3-day and 7-day ceftriaxone prophylaxis for cirrhotic patients with acute esophageal variceal bleeding. There was also no difference in 28 day survival rate between these two groups.